The house of the scorpion - Farmer, Nancy 1941- (Simon Pulse, 2002)
In a future where humans despise clones, Matt enjoys special status as the young clone of El Patron, the 142-year-old leader of a corrupt drug empire nestled between Mexico and the United States.